A case report and literature review of Churg–Strauss syndrome presenting with myocarditis. Issue 51 (December 2016) - Qiao, Lu; Gao, Dengfeng
Abstract: Background: Churg–Strauss syndrome (CSS) is a multisystem disorder characterized by asthma, prominent peripheral blood eosinophilia, and vasculitis signs. Case summary: Here we report a case of CSS presenting with acute myocarditis and heart failure and review the literature on CSS with cardiac involvement. A 59-year-old man with general fatigue, numbness of limbs, and a 2-year history of asthma was admitted to the department of orthopedics. Eosinophilia, history of asthma, lung infiltrates, peripheral neurological damage, and myocarditis suggested the diagnosis of CSS. Transthoracic echocardiography revealed a dilated hypokinetic left ventricle (left ventricular ejection fraction ∼40%) with mild segmental abnormalities in the septal and apical segments. Conclusion: By reviewing the present case reports, we concluded that (1) the younger age of CSS, the greater occurrence rate of complicating myocarditis and the poorer prognosis; (2) female CSS patients are older than male patients; (3) patients with cardiac involvement usually have a history of severe asthma; (4) markedly increased eosinophil count suggests a potential diagnosis of CSS (when the count increases to 20% of white blood cell counts or 8.1 × 109/L, eosinophils start to infiltrate into myocardium); and (5) negative ANCA status is associated with heart disease in CSS.